Evaluation as a situational or a universal good? Why evaluability assessment for evaluation systems is a good idea, what it might look like in practice, and why it is not fashionable - Dahler-Larsen, Peter (Scandinavian Journal of Public Administration, 2012)
Evaluability assessment is a diagnostic and prescriptive tool which helps evaluators determine whether evaluation is appropriate in a given situation. Thus, evaluation is understood as a situational good. Today, however, evaluability assessment is no longer particularly popular. Mandatory, comprehensive and repetitive evaluation systems are gaining ground in public administration supported by general social, political and managerial norms and values, indicating that evaluation is believed to be a universal good. Can a form of evaluability assessment be re-vitalized in order to pave the way for a more modest, more reflexive, and more context-sensitive belief in evaluation? The article offers a specific list of items in an updated version of evaluability assessment, and concludes with a discussion of the limitations of such approach.